FAULT LINKAGE IN CONTINENTAL RIFTS: STRUCTURE AND EVOLUTION OF A LARGE RELAY RAMP IN ZAVAROTNY; LAKE BAIKAL (RUSSIA) - Hus R.; De Batist M.; Klerkx J.; Matton C. (My University, 2006)
The internal structure of a large (10×40 km) relay ramp has been described between two border faults of the Baikal Rift Zone. The relay ramp, which is located partly onshore and partly offshore, has been investigated using a dense grid of high resolution seismic profiles and a digital terrain model containing topographic as well as bathymetric data. The structure of the relay ramp in Zavarotny is characterised by the development of secondary faults striking approximately parallel to the main faults. In combination with this, breaching occurred through the development of a new connecting fault. The breaching in Zavarotny has not lead to the destruction of the relay ramp, but a clear further evolution has been observed (e.g. a similar morphology of the lake floor and the basement inside the relay ramp, as well as the development of a second connecting fault). The strike direction of the secondary faults in the relay ramp has likely been influenced by the pre-existing basement fabric in the area. © 2006 Elsevier Ltd. All rights reserved.
Keywords: BAIKAL; BAIKAL RIFT ZONE; FAULT INTERACTION; FAULT LINKAGE; RELAY RAMP